International Practices of Registration and Use of Drugs for Gene Therapy in Clinical Practice - E. V. Melnikova; O. V. Merkulova; A. A. Chaplenko; O. A. Rachinskaya; V. A. Merkulov (Антибиотики и Химиотерапия)
The introduction of innovative products obtained using genetic engineering methods into clinical practice ensures the development of such a modern biomedicine area as gene therapy for, primarily, oncological, genetic, orphan diseases and other life threatening conditions, which have no effective treatment at present. Gene therapy is a combination of methods aimed at modifying patient's genetic material: outside the body (ex vivo gene therapy) or when the genetic engineered construct is introduced directly into the human body (in vivo gene therapy). In the legislation of most countries (USA, European Union, Japan, South Korea), products for gene therapy are regulated as biological drugs, whereas in the Russian Federation products for gene therapy in vivo are considered as biological drugs, and for ex vivo therapy - as biomedical cell products. Nowadays, more than 2,800 clinical trials of drugs for gene therapy have been conducted in the world. Regulators authorized 9 drugs for medical use, among which are the drugs for adoptive immunotherapy of blood cancer (Kymriah, Novartis; Yescarta, Kite Pharma, Gilead) based on chimeric antigen receptor technology for patients not responding to standard treatment methods. Development and marketing authorization of the drug Strimvelis (GSK) in the EU is a significant event in gene therapy. Strimvelis is used for the treatment of a genetic disease associated with mutation in the adenosine deaminase gene and leading to severe combined immunodeficiency. In the Russian Federation, to date, only one gene therapy drug, Neovasculgen (JSC Human Stem Cell Institute), based on plasmid DNA, for the treatment of atherosclerotic lower limb ischemia, has been included in the State Register of Medicines (since 2011). This review describes the experience of using drugs for gene therapy in international clinical practice, as well as the mechanisms for their marketing support after authorization by foreign regulatory authorities.